Povezovanje razbitega mesta - Ažman Momirski, Lučka (Urbani izziv, 1998)
The article begins with the exponential growth of the city Beirut between and after war in Lebanon. It is followed by postwar reconstruction of the city. Emphasis is placedon the city centre that was badly damaged during the war andreflections on the reestablishment of public life in the city and reflections on the understanding of transitory architecture, common in places where physical and social ties between the inhabitants were broken.
Keywords: Bejrut; mesta; urbanistično planiranje; urbanizam